2002
DOI: 10.1038/sj.gene.6363814
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to fibrocalculous pancreatic diabetes in Bangladeshi subjects: a family study

Abstract: Fibrocalculous pancreatic diabetes (FCPD) is an uncommon cause of diabetes, seen mainly in developing countries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
1
8
2
Order By: Relevance
“…Other groups have also demonstrated HLA associations with FCPD, although the disease-associated alleles are not always consistent between studies (Sanjeevi et al 1999). We have also found an association between the insulin gene hypervariable region and FCPD in southern Indian but not in Bangladeshi subjects (Kambo et al 1989;Chowdhury et al 2002).…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…Other groups have also demonstrated HLA associations with FCPD, although the disease-associated alleles are not always consistent between studies (Sanjeevi et al 1999). We have also found an association between the insulin gene hypervariable region and FCPD in southern Indian but not in Bangladeshi subjects (Kambo et al 1989;Chowdhury et al 2002).…”
contrasting
confidence: 53%
“…demonstrated familial clustering of the disease . More specifically, we have demonstrated associations between FCPD and human leukocyte antigen (HLA) genotype in subjects from southern India and Bangladesh, which revealed both similarities to and differences from T1D (Kambo et al 1989;Chowdhury et al 2002). Other groups have also demonstrated HLA associations with FCPD, although the disease-associated alleles are not always consistent between studies (Sanjeevi et al 1999).…”
mentioning
confidence: 88%
“…Another study found a positive association with DQ9 (A*0201-B*0303) [101]. In a family-based study, using TDT analysis, an overall association between TCP and HLA-DQB1 (P=0.003) was reported, that was largely due to a positive association with HLA-DQB1*0302 and a negative association with HLA-DQB1*0202 [102]. However, these findings should be interpreted with caution.…”
Section: Major Histocompatibility Complex (Mhc) Genesmentioning
confidence: 84%
“…Another study from India showed association of FCPD with DQ9 (A*0201-B*0303) [20]. Similarly, in Bangladesh, association was noted between FCPD and HLA-DQB1 [21].…”
Section: The Cassava Hypothesismentioning
confidence: 92%